The Commitment of the Company's Board of Directors to Act in Its Best Interest in the Age of Artificial Intelligence : A Comparative Study - Yousif, Alaa; Mohamed, Nashwa; Jalal, Ayad (Journal of Legal Sciences, 2025)
Artificial intelligence (AI) has gone beyond being a mere tool and has become an augmenter of the administrative activities of commercial company managers. This raises questions about the impact of AI on the board of directors' commitment to working to achieve the company's best interests. AI intervention raises significant issues stemming from its inherent nature. Its operation inevitably relies on specific inputs and control over its inputs and working mechanisms is not limited to the board of directors but encompasses multiple Interveners. Furthermore, a significant issue arises regarding the recommendations produced by AI: to what extent can the board of directors’ trust AI outputs, and how can it verify that they serve the company's best interests? Given the inadequacy of the general rules governing commercial companies to address the legal challenges posed by AI interference in company management, the study concludes that the UAE legislature must establish specific legal rules regulating the obligations of those involved in the operation of AI systems within the company. Which should ensure the fulfillment of the duty of loyalty, guarantee the quality of the inputs upon which AI operates, and establish applicable mechanisms for reviewing and monitoring AI outputs.